2012
DOI: 10.1111/j.1365-2265.2012.04336.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral cervical lymph node metastases in papillary thyroid cancer: a systematic review of imaging‐guided and prophylactic removal of the lateral compartment

Abstract: Metastatic cervical LNs were found in more than half of patients when prophylactic lateral LN dissection was performed. Use of conventional imaging for the selection of the surgical approach to the lateral cervical compartment may commonly identify stage N1a instead of N1b and thus lead to false stage assignment as stage III rather than stage IV, concealing the severe prognostic implications of this stage progression in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…The accuracy of ultrasound in the central compartment improves once the thyroid has been removed, in the follow-up setting. Ultrasound appears to have a higher sensitivity, ranging from 27 to 85 %, for the detection of lateral LNM with high variability among studies (LE 4) [45, 50]. Even with recent technological improvements in ultrasonography, the current preoperative evaluation of the central and lateral neck compartments is not as sensitive or specific as PND [48, 51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of ultrasound in the central compartment improves once the thyroid has been removed, in the follow-up setting. Ultrasound appears to have a higher sensitivity, ranging from 27 to 85 %, for the detection of lateral LNM with high variability among studies (LE 4) [45, 50]. Even with recent technological improvements in ultrasonography, the current preoperative evaluation of the central and lateral neck compartments is not as sensitive or specific as PND [48, 51].…”
Section: Resultsmentioning
confidence: 99%
“…Among the proponents of PND, there is also debate regarding the type of PND that should be performed (i.e., unilateral or bilateral PND of the central compartment) [50, 55]. Unilateral central compartment PND is performed in many centers with no worse outcome as compared to bilateral central PND.…”
Section: Resultsmentioning
confidence: 99%
“…According to the TNM staging system, the presence of lateral neck metastasis is classified as N1b and patients with N1b cancer and aged >45 years old are classified IV. Compared to the watch and wait approach [10,21,22], some clinicians are more proactive and perform lateral neck dissection [4,6,16,23]. Lateral neck dissection is already recommended by Japanese guidelines [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was also applied to thyroid cancer for early diagnosis and treatment [7,26,27] because the results of radiological examinations and FNA guided by B-mode ultrasound were not satisfactory [28,29]. The sensitivity of ultrasound and CT for the detection of lateral neck metastases is poor (27%) [4]. Kang concluded that patients with image-based, isolated lateral Level IV involvement and no macroscopic extra nodal extension are potential candidates for limited Levels III–IV dissection [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation